Analysis of Naturally Occurring Radioactive Material (NORM) in shifting earth layers in Piyungan, Bantul - Iqbal Nurrahim; Andang Widi Harto; Yohannes Sardjono; Isman Mulyadi Triatmoko; Zuhdi Ismail; Gede Sutresna Wijaya (Nuclear Engineering and Technology)
In recent decades, understanding the correlation between radon gas emissions and geodynamic processes has been pivotal in enhancing geophysical monitoring. This study advances current methodologies by refining radon data analysis and employing mathematical models to further elucidate this relationship. We developed a radon well geometry for Piyungan using Finite Element Method principles, and conducted simulations via GNU Octave to assess normal and anomalous conditions. The results indicate a basal radon concentration of 2.2420 Bq/L at a depth of 14.2308 m. Notably, radon levels inversely correlate with the water volume and diffusivity, yet proportionally increase with soil moisture. These findings offer a nuanced understanding of radon behavior in response to geodynamic activity, paving the way for improved environmental monitoring.